2019
DOI: 10.1111/birt.12474
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of trial of labor after cesarean birth by provider type in low‐risk women

Abstract: Background One approach to decreasing the cesarean birth rate in the United States is to increase the availability of birth attendants, including certified nurse‐midwives (CNMs), who offer trial of labor after cesarean (TOLAC). We examined associations between provider type and mode of birth for women attempting vaginal birth after cesarean (VBAC). Methods We performed a retrospective cohort study at a United States academic medical center using prospectively‐collected data (2005‐2012). We included healthy wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…This study revealed that women who accessed CoC with a midwife were significantly more likely to have an active and upright labour and birth, and to have a water birth. This supports previous research from the US comparing intrapartum care and experiences of women with obstetric or midwifery care [73][74][75][76]. The 2019 US study of 2539 women found that women who had a midwife attend their births had significantly fewer medical interventions during labour and birth and were more likely to use non-pharmacological comfort measures during labour and birth [73].…”
Section: Active Laboursupporting
confidence: 79%
“…This study revealed that women who accessed CoC with a midwife were significantly more likely to have an active and upright labour and birth, and to have a water birth. This supports previous research from the US comparing intrapartum care and experiences of women with obstetric or midwifery care [73][74][75][76]. The 2019 US study of 2539 women found that women who had a midwife attend their births had significantly fewer medical interventions during labour and birth and were more likely to use non-pharmacological comfort measures during labour and birth [73].…”
Section: Active Laboursupporting
confidence: 79%
“…Regardless of method, it is difficult to determine whether a hospital offers LAC or not; a 2012 survey of hospitals in California listed as a limitation that while a hospital could have a policy in place that allowed LAC, the actual day-to-day availability of LAC was driven by individual provider preferences (Barger et al, 2013). We lacked the data to account for provider-level effects on LAC, and these can have important effects on both availability and success (Fore, Allshouse, Carlson, & Hurt, 2020;Korst et al, 2011;Wells, 2010). As described in the methods section, using LAC frequency and LAC success to designate a hospital as "offering LAC" remains a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The United States' cesarean delivery rate climbed from 5% to 31.9% between 1970 and 2016. This dramatic increase was caused by several changes in the practice environment, including the implementation of electronic fetal monitoring and a decrease in operative vaginal deliveries and vaginal breech attempts [6,12]. In the United States, rates of vaginal birth after cesarean delivery have begun to rise again, from a low of about 8.4% of all births in 2008 and 2009 to 11.3% in 2014; in British Columbia, Canada, the proportion of women who had previously had a cesarean delivery who were considered eligible for vaginal birth after cesarean delivery increased from 75% in 2010 to 80% in 2014 [13].…”
Section: Issn: 2579-0730mentioning
confidence: 99%
“…The difference in results between the current study and the prior study is most likely due to differences in study designs, particularly because the previous study was a systematic review and the current study is a retrospective cohort analysis. TOLAC is regarded as a safe method of delivery for both women and newborns [12]. TOLAC, on the other hand, is known to raise the chance of uterine rupture.…”
Section: The Outcomes Among Women Who Underwent Trial Of Labor After ...mentioning
confidence: 99%